Effectiveness of Licorice Extract (Glycyrrhiza glabra L.) on Traumatic Ulcer with Parameter Study: Macrophage, Neutrophil, and Lymphocyte - Liftia Layyinatus Syifa; Rina Kartika Sari; Dea Maynur Shalima Ismail; Rizqila Diva Pradisha (Faculty of Dentistry, Universitas Islam Sultan Agung, 2026)
Background: Traumatic oral ulcers are common lesions characterized by epithelial loss, pain, and erythematous halos. Healing occurs through four stages: haemostasis, inflammation, proliferation, and remodelling. Licorice root (Glycyrrhiza glabra L.) is known for its anti-inflammatory and immunomodulatory properties. This study aimed to evaluate the effectiveness of licorice extract at various concentrations on macrophage, neutrophil, and lymphocyte cell counts during traumatic ulcer healing.Methods: A post-test only group design was used with five groups: three treatment groups receiving 5%, 10%, and 15% licorice extract, and two control groups (positive: Aloclair; negative: aquadest), each with six mice. Ulcers were induced using a heated burnisher on the labial mucosa. Treatments were applied twice daily using a nano mouth spray. After euthanasia, labial tissues were fixed, processed, and stained with Hematoxylin-Eosin for histological examination under 400× magnification.Result: Phytochemical analysis revealed high flavonoid (44.669) and saponin (38.802) contents in licorice extract. Statistical tests showed significant differences (p < 0.05) in macrophage, neutrophil, and lymphocyte counts among groups. The 10% extract group showed the highest immune cell response, suggesting optimal anti-inflammatory and immunomodulatory effects at this concentration.Conclusion: Licorice extract effectively promotes the healing of traumatic oral ulcers. Among tested concentrations, the 10% extract provided the best therapeutic effect, accelerating healing and regulating inflammatory cell activity more effectively than other doses or controls.